Penerapan Model PMRI Berbantuan Media PAPABICA terhadap Kemampuan Berpikir Kritis Siswa - Ihsan, Adliy; Ermawati, Diana; Riswari, Lovika Ardana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study is motivated by the low critical thinking ability of grade V students of SDN Sumbersoko 02 in Mathematics learning. Critical thinking skills are important skills that students need to have to solve problems logically and systematically. This study aims to measure the difference in the average value of students' critical thinking skills before and after the application of the Indonesian Realistic Mathematics Education (PMRI) model with the help of the Numbering Board (PAPABICA) media. The method used is quantitative with a one group pre-test post-test design. Data was collected through interviews, observations, documentation, and tests, then analyzed using normality tests and paired sample t-tests. The results of the study showed a significant increase in students' critical thinking skills. This can be seen from the increase in the average pretest score by 54.16 to 84.33 in the posttest, with the results of the normality test (Shapiro-Wilk) of 0.215 (pretest) and 0.14 (posttest), both > 0.05. The t-test yielded a significance of 0.000 < 0.05, so Ha was accepted and Ho was rejected. It can be concluded that the implementation of PMRI assisted by PAPABICA is effective in improving students' critical thinking skills. So that the conclusion that can be drawn is that there is a difference in the average value of students' critical thinking skills before and after the implementation of the PMRI model with the help of PAABICA media. These findings provide an interactive and applicable alternative Mathematics learning strategy for elementary school teachers.